The Effect of Robotics Education on Gender Differences in STEM Attitudes among Dutch 7th and 8th Grade Students - Nora van Wassenaer; Jos Tolboom; Olivier van Beekum (Education Sciences, 2023)
Because of its hands-on and integrative approach to STEM, educational robotics has become increasingly popular in recent years. Yet, a gender gap still exists in attitudes towards STEM studies and careers, especially among middle and high school students, potentially resulting in a lack of women in the STEM workforce. This study explores the effect of a robotics curriculum on Dutch 7th- and 8th-grade students’ attitude towards STEM subjects and careers, as assessed by the S-STEM survey. The results revealed no difference between the pre-test and post-test in attitudes toward STEM for both boys and girls. However, boys scored significantly higher than girls on attitude towards technology, engineering and future STEM studies on the post-test. A post hoc analysis revealed a significant difference between boys and girls on their attitude towards engineering and technology during the pre-test. These results demonstrate the difference between boys and girls in their attitudes towards STEM subjects and careers within the context of robotics education. Considering the lack of research on educational robotics among young teenagers, this field needs to be further studied to assess its effect on gender differences within attitudes towards STEM.